Impact of extreme heat and heatwaves on children's health: A scoping review - Laura H Schapiro; Mark A McShane; Harleen K Marwah; Megan E Callaghan; Mandy L Neudecker (The Journal of Climate Change and Health, 2024)
Introduction: Due to climate change, the frequency of heatwaves and extreme heat events (EHE) has increased over the last five decades and is expected to continue increasing. Methods: In this scoping review, we searched the literature for how EHEs and heatwaves impact pediatric health and how children can adapt to these threats. We used the PRISMA Extension for Scoping Reviews framework and searched several databases for studies pertaining to pediatric health, heatwaves, and EHEs. Results: The search generated 1719 studies that were screened by the authors. Ultimately, 113 studies were included in this review. We found that extreme heat exposure leads to a variety of adverse health outcomes in pediatric patients; some of the most notable are increased risks of adverse birth outcomes, including preterm birth and low birth weight. Extreme heat exposure was also associated with increased rates among children of emergency department visits, asthma exacerbations, heat illness, and impaired school performance. Conclusion: Children will continue to face the repercussions of extreme heat as global temperatures continue to rise. It is imperative that future research includes adaptation measures to help keep children healthy and safe during periods of extreme heat.